Risk Assessment and Mitigation Strategies for Developing High-Rise Building Projects in Kathmandu Valley - Yadav, Sanjeet kumar (My University, 2026)
Kathmandu Valley high population and blistering rate of urbanisation has come forth in collaboration of location explosion of high-rise construction projects, which are a considerable contribution to the expansion of the urban areas in addition to economic progress. It also has a high possibility of operational risk to the implementation of such projects, which has been mostly ignored by most in place of structural, environmental or financial risks. The purpose of this research is to identify and to investigate operational risks of the high-rise construction in Kathmandu Valley. It presents the study within the context of the operational risk management and the PESTEL model that talks about political, economic, social, technological, environmental or legal factors that affect the construction industry within Kathmandu. Qualitative methodology has been used and that is via case study methodology. Data were collected by using open ended questionnaires with project managers, engineers and other professionals in the construction industry working on the high-rise projects and was complemented with secondary sources. The identification of recurrent patterns and issues under which the construction stakeholders were facing involved the use of thematic analysis. The findings reveal that operational risks related to Kathmandu based high-rise construction projects include, earthquake vulnerability, labour unavailability, unsafe working conditions, site congestion, late procurement, use of foreign materials, regulatory, and communication. The urban, institutional and economic landscape of the region influences such risks. Planning, safety training, coordination of stakeholders and observation of regulations through identification, prioritisation, and mitigation of risks are process undertaken by project managers proactively. The conclusion of the study is that Operation risk management must be included in the planning of high rise projects in Kathmandu valley. This can be obtained through learning how to conduct efficient risk assessment, improvement of safety culture, labour training, improve supply chain strategies, greater digital monitoring and advanced, timely regulatory engagement to achieve better project outcomes. This research provides valuable insights to the professionals in the construction industry and policymakers on how to manage the risks of operating in a relatively fast-growing, urbanising and seismically active urban environment. KEYWORDS: Operational risk, high-rise construction, Kathmandu Valley, PESTEL analysis, risk management, occupational health and safety, supply chain, regulatory compliance.
Keywords: risk management; risks; industrial safety; projects; project management; Kathmandu; construction industry; safety and security; supply chains; construction; Strategic Project Management; Master’s Programme in Industrial Engineering and Management